2006
DOI: 10.1007/s10549-006-9439-x
|View full text |Cite
|
Sign up to set email alerts
|

Provider’s volume and quality of breast cancer detection and treatment

Abstract: For many health conditions, the process or result of medical procedures improves with increasing caseload. The evidence about breast cancer has not been thoroughly assessed. This review synthesizes the literature about provider's volume and performance in either breast cancer screening with mammography or treatment. Articles published in English between 1990 and 2006 were identified by a computerized search and by review of reference lists. In screening with mammography, the reading volume of the radiologist a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 84 publications
(193 reference statements)
1
9
1
Order By: Relevance
“…The comparison of responses from both sub‐groups for the Likert ratings of difficulty making a ‘normal’ decision and the assessment of cases on suitability for a single reading strategy, demonstrated similar responses. Although recent studies suggested that readers' performance in reading screening mammograms increased with the number of mammograms read per year, this was not observed in this study. It appears that responses in this study were not driven by reader experience, which was defined by reading volume.…”
Section: Discussioncontrasting
confidence: 94%
“…The comparison of responses from both sub‐groups for the Likert ratings of difficulty making a ‘normal’ decision and the assessment of cases on suitability for a single reading strategy, demonstrated similar responses. Although recent studies suggested that readers' performance in reading screening mammograms increased with the number of mammograms read per year, this was not observed in this study. It appears that responses in this study were not driven by reader experience, which was defined by reading volume.…”
Section: Discussioncontrasting
confidence: 94%
“…[4][5][6] Previous studies based on high-risk procedures have discovered that operative or in-hospital mortality rates are lower in high-volume hospitals. [10][11][12][13][14][15][16][17][18] The differences for post-RFA morbidity and mortality between high-volume and low-volume hospitals may be limited because of the low complication rates attributable to RFA. The influence of hospital volume on late survival cannot be fully explained using differences in post-RFA morbidity and mortality and should be attributed to other factors.…”
Section: Discussionmentioning
confidence: 99%
“…7,8 The relation between tumor volume and outcome has been widely discussed in past decades, and previous studies have verified this relation in various procedures. [9][10][11] For procedures that depend greatly on technique, such as cancer surgery (including hepatectomy for HCC), hospital volume not only has been associated with decreased treatment-related mortality and complication rates, [12][13][14][15][16][17][18] it also has been associated with better long-term survival rates. [19][20][21][22][23][24][25][26] A successful percutaneous RFA for HCC relies heavily on physician technique, because the procedure requires the insertion of a needle electrode directly into the lesion using imaging guidance (ultrasound or computed tomography).…”
Section: Introductionmentioning
confidence: 99%
“…The Breast Cancer Surveillance Consortium (BCSC) registries and Statistical mammography performance and volume, although inconsistent, generally suggest that higher-volume readers have lower false-positive rates (FPRs); findings on sensitivity are mixed (3). To address these gaps between observed and optimal screening accuracy (1), previous studies examined the relationship between interpretive volume and screening and diagnostic performance (4,5).…”
Section: Subjectsmentioning
confidence: 99%